Toward a Medical Gastric Bypass: Chronic Feeding Studies With Liraglutide + PYY3-36 Combination Therapy in Diet-Induced Obese Rats - Dischinger, Ulrich; Hasinger, Julia; Königsrainer, Malina; Corteville, Carolin; Otto, Christoph; Fassnacht, Martin; Hankir, Mohamed; Seyfried, Florian Johannes David (Frontiers in Endocrinology, 2021)
Background: Combination therapies of anorectic gut hormones partially mimic the beneficial effects of bariatric surgery. Thus far, the effects of a combined chronic systemic administration of Glucagon-like peptide-1 (GLP-1) and peptide tyrosine tyrosine 3-36 (PYY3-36) have not been directly compared to Roux-en-Y gastric bypass (RYGB) in a standardized experimental setting. Methods: High-fat diet (HFD)-induced obese male Wistar rats were randomized into six treatment groups: (1) RYGB, (2) sham-operation (shams), (3) liraglutide, (4) PYY3-36, (5) PYY3-36+liraglutide, (6) saline. Animals were kept on a free choice high- and low-fat diet. Food intake, preference and body weight were measured daily for 4 weeks. Open field (OP) and elevated plus maze (EPM) tests were performed. Results: RYGB reduced food intake and achieved sustained weight loss. Combined PYY3-36+liraglutide treatment led to similar and plateaued weight loss compared to RYGB. Combined PYY3-36+liraglutide treatment was superior to PYY3-36 (p ≤ 0.0001) and liraglutide (p ≤ 0.05 or p ≤ 0.01) mono-therapy. PYY3-36+liraglutide treatment and RYGB also reduced overall food intake and (less pronounced) high-fat preference compared to controls. The animals showed no signs of abnormal behavior in OF or EPM. Conclusions: Liraglutide and PYY3-36 combination therapy vastly mimics reduced food intake, food choice and weight reducing benefits of RYGB.